TRANSLATION OF IDIOMATIC EXPRESSION IN ROALD DAHL’S SHORT STORY “MAN FROM THE SOUTH“ FROM ENGLISH INTO INDONESIAN - Lilis Susanti; Yuli Kuswardani (Universitas PGRI Madiun, 2015)
This research describes the translation strategy of idiomatic expression used by translator and the quality of translation of idiomatic expression in the short story by Roald Dahl entitled “Man from the South”. This research uses descriptive qualitative method and uses content analysis as the data collection technique. To check the validity of this research, the researcher uses triangulation such as, data triangulation, investigator triangulation, theory triangulation, and methodological triangulation. The results of this research shows that several translation strategies are applied, which include idioms of similar meaning and form, translation by paraphrase, and translation by omission. In this research, paraphrase strategy is in the most applied strategy87.88% of the data (58 idiomatic expressions) use translation by paraphrase. This research also shows that the quality of translation of idiomatic expression translation which consists of accuracy, naturalness, and clarity is categorized as good translation. It can be seen from the results that 75% of the data are accurate, 78, 79% of the data are natural, and78, 79% of the data are clear.